Worlds Maailmat 90. (Joensuu : Joensuu Art Museum, 1990)
Miyajima, Tatsuo ; Ngwenya, Malangatana ; Lasker, Jonathan ; Steinbach, Haim ; Tjakamarra, Michael Nelson ; Bianchi, Domenico ; Gudmundsson, Kristjan ; Trockel, Rosemarie ; Zatulovskaja, Irina ; Wirkkala, Maaria
Worlds Maailmat 90, Joensuu Art Museum, Joensuu, 1990
boek